2003
DOI: 10.1002/hon.703
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence of non‐Hodgkin's lymphoma in Canada, 1970–1996: age–period–cohort analysis

Abstract: Previous studies have shown that the incidence of non-Hodgkin's lymphoma (NHL) has increased in many parts of the world in recent decades. Using data obtained from the Canadian Cancer Registry, the present study examined time trends in NHL incidence in Canada between 1970 and 1996 and the effects of age, period of diagnosis and birth cohort on incidence patterns for each sex separately. Results showed that overall age-adjusted incidence rates increased substantially, from 7.3 and 5.2 per 100,000 in 1970-1971 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 29 publications
3
27
0
6
Order By: Relevance
“…12 A recent age-period-cohort analysis of incidence rates of NHL in Canada between 1970 and 1996 found that changes in NHL rates over this time period could not be fully explained by diagnostic improvements, changes in NHL classification and/or the increases in AIDS-related NHL, and suggested that increased exposure to risk factors may be important, although specific factors were not identified. 13 A study of temporal patterns of leukemias and lymphomas in children found that their incidence rates of NHL have been relatively stable. 14 The striking increase in NHL rates was not limited to the US.…”
Section: Descriptive Epidemiologymentioning
confidence: 99%
“…12 A recent age-period-cohort analysis of incidence rates of NHL in Canada between 1970 and 1996 found that changes in NHL rates over this time period could not be fully explained by diagnostic improvements, changes in NHL classification and/or the increases in AIDS-related NHL, and suggested that increased exposure to risk factors may be important, although specific factors were not identified. 13 A study of temporal patterns of leukemias and lymphomas in children found that their incidence rates of NHL have been relatively stable. 14 The striking increase in NHL rates was not limited to the US.…”
Section: Descriptive Epidemiologymentioning
confidence: 99%
“…A remarkable increase in the incidence of non-Hodgkin's lymphomas (NHL) has been observed during the second half of the 20th century, almost ubiquitous and for almost as long as official statistics have been available (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In several countries, including the Nordic, NHL has been among the most rapidly increasing malignancies and now accounts for 4% of all new cancer cases in the United States (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the diagnostic practice over time and the emergence of acquired immunodeficiency syndrome (AIDS) pandemic in the early 1980s contributed to the rise of NHL but are not sufficient to explain the dramatic increase in incidence of the lymphomas. The use of immunosuppression including corticosteroids, immunomodulators, and chemotherapy in organ transplant recipients, in connective tissue disorders, but also in the less severe dermatologic diseases like psoriasis or atopic dermatitis, has also influenced the steep rise in incidence of these lymphoproliferative disorders [24,[26][27][28][29][30]. Recent reports suggest that the rise in incidence may have slowed in the late 1990s.…”
Section: Discussionmentioning
confidence: 99%